BCc1, the novel antineoplastic nanocomplex, showed potent anticancer effects in vitro and in vivo - Kalanaky S; Hafizi M; Fakharzadeh S; Vasei M; Langroudi L; Janzamin E; Hashemi SM; Khayamzadeh M; Soleimani M; Akbari ME; Nazaran MH (Drug Design, Development and Therapy, 2015)
Somayeh Kalanaky,1,2 Maryam Hafizi,1–3 Saideh Fakharzadeh,1 Mohammad Vasei,4 Ladan Langroudi,5 Ehsan Janzamin,6 Seyed Mahmoud Hashemi,7 Maryam Khayamzadeh,2 Masoud Soleimani,6 Mohammad Esmaeil Akbari,2 Mohammad Hassan Nazaran1 1Department of Research and Development, Sodour Ahrar Shargh Company, Tehran, Iran; 2Cancer Research Centre, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 3Stem Cell Technology Research Center, Tehran, Iran; 4Department of Pathology, Tehran University of Medical Sciences, Tehran, Iran; 5Department of Immunology, Faculty of Medical Sciences, Tarbiat Modares University, Tehran, Iran; 6Department of Haematology, Faculty of Medical Sciences, Tarbiat Modares University, Tehran, Iran; 7Department of Immunology, Faculty of Medicine, Shahid Beheshti University of Medical Sciences, Tehran, Iran Purpose: In spite of all the efforts and researches on anticancer therapeutics, an absolute treatment is still a myth. Therefore, it is necessary to utilize novel technologies in order to synthesize smart multifunctional structures. In this study, for the first time, we have evaluated the anticancer effects of BCc1 nanocomplex by vitro and in vivo studies, which is designed based on the novel nanochelating technology.Methods: Human breast adenocarcinoma cell line (MCF-7) and mouse embryonic fibroblasts were used for the in vitro study. Antioxidant potential, cell toxicity, apoptosis induction, and CD44 and CD24 protein expression were evaluated after treatment of cells with different concentrations of BCc1 nanocomplex. For the in vivo study, mammary tumor-bearing female Balb/c mice were treated with different doses of BCc1 and their effects on tumor growth rate and survival were evaluated.Results: BCc1 decreased CD44 protein expression and increased CD24 protein expression. It induced MCF-7 cell apoptosis but at the same concentrations did not have negative effects on mouse embryonic fibroblasts viability and protected them against oxidative stress. Treatment with nanocomplex increased survival and reduced the tumor size growth in breast cancer-bearing balb/c mice.Conclusion: These results demonstrate that BCc1 has the capacity to be assessed as a new anticancer agent in complementary studies. Keywords: BCc1, cancer, nanotechnology, nanochelating technology, nanocomplex